2019
DOI: 10.1002/sctm.19-0193
|View full text |Cite
|
Sign up to set email alerts
|

Are all stem cells equal? Systematic review, evidence map, and meta-analyses of preclinical stem cell-based therapies for bronchopulmonary dysplasia

Abstract: Regenerative stem cell-based therapies for bronchopulmonary dysplasia (BPD), the most common preterm birth complication, demonstrate promise in animals. Failure to objectively appraise available preclinical data and identify knowledge gaps could jeopardize clinical translation. We performed a systematic review and network metaanalysis (NMA) of preclinical studies testing cell-based therapies in experimental neonatal lung injury. Fifty-three studies assessing 15 different cell-based therapies were identified: 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 90 publications
(430 reference statements)
0
23
0
Order By: Relevance
“…Ongoing investigations within the baboon model of borderline viability are suitable to confirm the results from rodents and can help to determine functional improvements in more detail than mouse or rat models [ 120 ]. For these reasons, the just published meta-analysis was not able to provide final conclusions [ 69 ]. The robust comparison of different therapeutic approaches and the standardization of experimental settings are necessary prerogatives to dissolve these unanswered questions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ongoing investigations within the baboon model of borderline viability are suitable to confirm the results from rodents and can help to determine functional improvements in more detail than mouse or rat models [ 120 ]. For these reasons, the just published meta-analysis was not able to provide final conclusions [ 69 ]. The robust comparison of different therapeutic approaches and the standardization of experimental settings are necessary prerogatives to dissolve these unanswered questions.…”
Section: Discussionmentioning
confidence: 99%
“…The studies in rodents were systematically reviewed in the meantime and came to the conclusion that MSC have a robust and overall positive effect on the pulmonary outcome. Beneficial effects were stated for initial and delayed MSC application and different sources, dosages and routes of exogenous MSC application as detailed above [ 65 , 69 ]. Benefits of MSC therapy were not restricted to the lung but also included reduced brain injury among others even when applied topically to the lung.…”
Section: Is the Therapeutic Efficacy Of Msc To Prevent Or Treat Bpmentioning
confidence: 99%
“…The precise mechanism by which they act is not completely known; however, it is believed that MSCs act primarily via a paracrine effect 63 . In a systematic review evaluating the various cell‐based therapies in preclinical BPD, MSCs were found to be the most efficacious among all interventions, although they were exclusively investigated in the rodent hyperoxia-exposed model of BPD 64 . Human umbilical cord tissue and cord blood have been identified as a potential source of MSCs and have been further explored as a feasible source of these cells and exosomes 65 , 66 .…”
Section: New and Upcoming Therapies In The Management And Prevention mentioning
confidence: 99%
“…This year, Augustine et al published a network meta-analysis comparing stem cell and cell-free therapies in preclinical measures of BPD. MSC-CdM had a similar effect size to MSCs regarding alveolarization (MSC SMD 1.71 vs. CdM SMD1.68), angiogenesis (SMD 2.24 vs. 1.79), and pulmonary remodeling (1.29 vs. 1.22) [ 39 ]. Similar to their results, this review showed that CdM had among the largest impact on measures of alveolarization and vasculogenesis, processes critical for appropriate lung healing, development, and function [ 40 ].…”
Section: Discussionmentioning
confidence: 99%